The Precedents of University’s Parcel Service Quality Towards Student Satisfaction in a Higher Education Institution using SERVQUAL Model: A Conceptual Framework - Mohamad Hazeem Sidik; Muhammad Ashlyzan Bin Razik; Md Zaki Bin Muhamad Hasan; Norlinda Rozar; Abdurrahman Faris Indriya Himawan (Universitas Muhammadiyah Gresik, 2023)
Service quality is among the most crucial determinant for customer satisfaction in the parcel service industry. It consists of tangibility, reliability, assurance, empathy and responsiveness. However, there is lack of research and knowledge available on the customer satisfaction with the parcel service especially in higher education level. The purpose of the research is to develop a SERVQUAL framework on student satisfaction with University’s Parcel Service Quality in a higher education institution. Therefore, this paper can act as benchmark for parcel services to checklist their quality. Future researcher can use this research as the foundation and reference about the precedents of the university’s parcel service toward the customer/student satisfaction.